Application of literate-programming principles for the description of a FORTRAN 90 extension to quaternion arithmetic. - Atlamazoglou, Prodromos E.; Anastassiu, Hristos T.; Kaklamani, Dimitra I.
In an effort to effectively annotate and document a FORTRAN 90 module that extends the language's mathematical capabilities to the performance of quaternion operations, the literate-programming paradigm is adopted. The basic principles of this paradigm are discussed through a short introduction to the features of a specific literate-programming system known as FWEB. This system is then employed for the efficient presentation of the FORTRAN 90 quaternion arithmetic module.
Keywords: Mathematical programming; Object oriented programming; Computer languages; Literate programming; Quarternions; Digital arithmetic; Documentation